Comparative effect of antihypertensive drugs in improving arterial stiffness in adults with hypertension (RIGIPREV study). A network meta-analysis - Cavero-Redondo, Iván; Saz-Lara, Alicia; Lugones-Sánchez, Cristina; Pozuelo-Carrascosa, Diana P.; Gómez-Sánchez, Leticia; López-Gil, José Francisco; García-Ortiz, Luis; Bruno, Rosa Maria; Gómez-Marcos, Manuel Ángel (Frontiers in Pharmacology, 2023)
To synthesize and evaluate the available scientific evidence on the efficacy of antihypertensive drugs on arterial stiffness in patients with hypertension by using a network meta-analysis approach.Methods: A systematic search of the MEDLINE (via PubMed), Scopus, and Web of Science databases was conducted to identify experimental studies addressing the effect of different antihypertensive drugs on arterial stiffness parameters (pulse wave velocity [PWV] and augmentation index [AIx]) in adults with hypertension. Comparative evaluation of the effect of antihypertensive drugs was performed by conducting a standard pairwise meta-analysis and a network meta-analysis for direct and indirect This is a provisional file, not the final typeset article comparisons between antihypertensive drugs and placebo/other antihypertensive drugs. Analyses were performed including studies of any duration and only studies longer than 6 months length.Seventy-six studies were included in the main analysis and considering only studies longer than 6 months length, thiazide diuretics, ACEIs, ARBs, the ACEI/ARB combination, the ACEI/CCB combination, and the ARB/CCB combination showed a higher effect on reducing PWV, and ACEIs and ARBs on reducing AIx.Our research provides evidence that antihypertensive medications are an effective way to treat arterial stiffness in adults with hypertension. Based on our findings, patients with hypertension who have greater levels of arterial stiffness may benefit from using thiazide diuretics, ACEIs, ARBs, the ACEI/ARB combination, the ACEI/CCB combination, and the ARB/CCB combination.